Monetary policy and microfinance credit risk: the case of peru, period 2003-2021 - Calsin Enriquez, Hugo Oscar (2023)
Financial and/or credit crises generate questioning of the role of Central Banks and their intervention effectiveness, therefore, it is necessary to study the role played by this type of institution in the planning of the main policies within the framework of the COVID-19 crisis and its impact on the stability of the financial system. The objective of the research is to determine the influence of monetary policies on credit risks between 2003 and 2021. The methodology employed consisted of an explanatory, causal and quantitative approach, with a non-experimental and parametric design, applying a VAR risk model, through the Generalized Method of Moments (GMM) and 2-stage least squares method (2SLS). We work with the time series database of the Central Reserve Bank of Peru (BCRP) and the Superintendence of Banking and Insurance (SBS). The results within the model show that the coefficient of the influence of the expansionary monetary policy applied has a significant impact on the increase of credit risk and vice versa.